2022
DOI: 10.3389/fnmol.2022.932955
|View full text |Cite
|
Sign up to set email alerts
|

Novel therapeutic modulators of astrocytes for hydrocephalus

Abstract: Hydrocephalus is mainly characterized by excessive production or impaired absorption of cerebrospinal fluid that causes ventricular dilation and intracranial hypertension. Astrocytes are the key response cells to inflammation in the central nervous system. In hydrocephalus, astrocytes are activated and show dual characteristics depending on the period of development of the disease. They can suppress the disease in the early stage and may aggravate it in the late stage. More evidence suggests that therapeutics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 108 publications
(130 reference statements)
0
4
0
Order By: Relevance
“…The role of astrocytes in hydrocephalus is not conclusive. 72 It is reported that in an animal model of hyh mice, astrocytes form a layer at the denuded ventricular lining, 44 supporting that astroglial reaction may compensate for the loss of homeostasis. 73 However, in a mouse model of Bardet–Biedl syndrome (BBS) caused by BBS8 deletion, the enhanced GFAP protein correlates with the development of hydrocephalus, 74 suggesting that astrocytes play a role in causing this phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The role of astrocytes in hydrocephalus is not conclusive. 72 It is reported that in an animal model of hyh mice, astrocytes form a layer at the denuded ventricular lining, 44 supporting that astroglial reaction may compensate for the loss of homeostasis. 73 However, in a mouse model of Bardet–Biedl syndrome (BBS) caused by BBS8 deletion, the enhanced GFAP protein correlates with the development of hydrocephalus, 74 suggesting that astrocytes play a role in causing this phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Reactive astrogliosis was observed throughout the cerebral mantle. 14 These changes, particularly pronounced in advanced hydrocephalus, indicated the significant impact of hydrocephalus on CBF and associated brain alterations. 2,38 This study did not find a significant increase in ICP in the hydrocephalic group compared with the control group, and there was no significant correlation between ICP and CBF.…”
Section: Discussionmentioning
confidence: 99%
“…Reactive astrogliosis was observed throughout the cerebral mantle. 14 These changes, particularly pronounced in advanced hydrocephalus, indicated the significant impact of hydrocephalus on CBF and associated brain alterations. 2,38…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation